2020
DOI: 10.1097/dad.0000000000001795
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic Neoplasms With MAP2K1 in Frame Deletions and Spitz Morphology

Abstract: With the advent of better molecular characterization of Spitz melanocytic neoplasms, there has been increasing effort to better understand and describe the relationships between specific driver fusion and/or mutations with the clinical and histomorphological characteristics of the lesions. Structural rearrangements in mitogen activated protein kinase genes have recently been noted to be important in Spitz neoplasms. Only very few reports, however, have described in detail melanocytic tumors with in frame delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 30 publications
3
33
1
Order By: Relevance
“…In addition, genes encoding protein tyrosine kinases, KIT and EPHA5 , relevant receptors upstream of the MAPK pathway, are particularly highly expressed in the melanoma compared to BAP1 -inactivated nevus. Interestingly, a mutation in the MAP2K1 gene was identified in the BAPoma from our patient; similar mutations in this gene have been reported in a large spectrum of melanocytic lesions, including BAPomas [ 21 ].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, genes encoding protein tyrosine kinases, KIT and EPHA5 , relevant receptors upstream of the MAPK pathway, are particularly highly expressed in the melanoma compared to BAP1 -inactivated nevus. Interestingly, a mutation in the MAP2K1 gene was identified in the BAPoma from our patient; similar mutations in this gene have been reported in a large spectrum of melanocytic lesions, including BAPomas [ 21 ].…”
Section: Discussionsupporting
confidence: 83%
“…are mostly associated with Spitz lesions, whereas mutations are typical for conventional melanocytic lesions. However, there are well-known exceptions such as HRAS mutation in desmoplastic Spitz nevus and MAP2K1 mutations in Spitz lesions [35][36][37] . RAF proto-oncogene serine/threonineprotein kinase encoded by RAF1 functions as an alternative MAPK signaling mechanism as it forms dimers with wild-type BRAF 38 .…”
Section: Discussionmentioning
confidence: 99%
“…One of these, the C125S variant, was previously identified in melanoma patients who developed resistance to BRAF inhibitors [ 25 , 26 ]. In a recent study, MAP2K1 alterations were reported in neoplasms with heterogeneous cell morphology, including melanocytic tumors with Spitz cytomorphology, DPN-like architecture with a plexiform pattern, and heavy melanization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%